2014
DOI: 10.1038/onc.2014.406
|View full text |Cite
|
Sign up to set email alerts
|

The landscape and therapeutic relevance of cancer-associated transcript fusions

Abstract: Transcript fusions as a result of chromosomal rearrangements have been a focus of attention in cancer as they provide attractive therapeutic targets. To identify novel fusion transcripts with the potential to be exploited therapeutically, we analyzed RNA sequencing, DNA copy number and gene mutation data from 4,366 primary tumor samples. To avoid false positives, we implemented stringent quality criteria that included filtering of fusions detected in RNAseq data from 364 normal tissue samples. Our analysis ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
463
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(496 citation statements)
references
References 54 publications
22
463
0
1
Order By: Relevance
“…The genes NINJ2 , PAK1, PCMTD1, SNTB1 , and ZNF512 were also found fused with different partners in HGSC (Figure 4). 5 Taking all these results together, we see that all the mentioned genes were recurrently rearranged in ovarian cancer, admittedly at very low frequencies. Furthermore, 21 of the genes we found involved in fusions were previously reported in 35 different fusion transcripts in studies of breast cancer and 14 fusion transcripts were identified in lung cancer5, 31, 32 (Table 3), hinting that they may be generally relevant in carcinogenesis of different types.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The genes NINJ2 , PAK1, PCMTD1, SNTB1 , and ZNF512 were also found fused with different partners in HGSC (Figure 4). 5 Taking all these results together, we see that all the mentioned genes were recurrently rearranged in ovarian cancer, admittedly at very low frequencies. Furthermore, 21 of the genes we found involved in fusions were previously reported in 35 different fusion transcripts in studies of breast cancer and 14 fusion transcripts were identified in lung cancer5, 31, 32 (Table 3), hinting that they may be generally relevant in carcinogenesis of different types.…”
Section: Discussionmentioning
confidence: 83%
“…The uniqueness of these fusion transcripts was checked against the Mitelman Database for Chromosome Aberrations and Gene Fusions in Cancer (https://cgap.nci.nih.gov/Chromosomes/Mitelman). Only the fusion transcripts KDMA5‐NINJ2 and NSD1‐ZNF346 were previously identified, by Yoshihara et al 5. in HGSC.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is a critical mediator of both estrogen‐stimulated proliferation of breast cancer cells and androgen‐stimulated proliferation of prostate cancer cells 13, 14. According to the Mitelman Database of Chromosome Aberrations and Gene Fusions in Cancer (http://cgap.nci.nih.gov/Chromosomes/Mitelman), GREB1 was previously found involved in various types of neoplasia and with different partners: a GREB1‐E2F6 fusion was seen in T‐cell acute lymphoblastic leukemia15 and a GREB1‐PDE1A in adenocarcinoma of the prostate 16. Although its exact function in the cascade of hormone action remains unclear, GREB1 may regulate proliferation in hormone responsive ovarian and endometrial cancer cells and thus be a candidate for further consideration as a potential therapeutic target 17…”
Section: Discussionmentioning
confidence: 99%